Screening for esophageal adenocarcinoma and precancerous conditions (dysplasia and Barrett’s esophagus) in patients with chronic gastroesophageal reflux disease with or without other risk factors: two systematic reviews and one overview of reviews to inform a guideline of the Canadian Task Force on Preventive Health Care (CTFPHC) - Hamel, Candyce; Ahmadzai, Nadera; Beck, Andrew; Thuku, Micere; Skidmore, Becky; Pussegoda, Kusala; Bjerre, Lise; Chatterjee, Avijit; Dennis, Kristopher; Ferri, Lorenzo; Maziak, Donna E; Shea, Beverley J; et al. (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Two reviews and an overview were produced for the Canadian Task Force on Preventive Health Care guideline on screening for esophageal adenocarcinoma in patients with chronic gastroesophageal reflux disease (GERD) without alarm symptoms. The goal was to systematically review three key questions (KQs): (1) The effectiveness of screening for these conditions; (2) How adults with chronic GERD weigh the benefits and harms of screening, and what factors contribute to their preferences and decision to undergo screening; and (3) Treatment options for Barrett’s esophagus (BE), dysplasia or stage 1 EAC (overview of reviews). Methods Bibliographic databases (e.g. Ovid MEDLINE®) were searched for each review in October 2018. We also searched for unpublished literature (e.g. relevant websites). The liberal accelerated approach was used for title and abstract screening. Two reviewers independently screened full-text articles. Data extraction and risk of bias assessments were completed by one reviewer and verified by another reviewer (KQ1 and 2). Quality assessments were completed by two reviewers independently in duplicate (KQ3). Disagreements were resolved through discussion. We used various risk of bias tools suitable for study design. The GRADE framework was used for rating the certainty of the evidence. Results Ten studies evaluated the effectiveness of screening. One retrospective study reported no difference in long-term survival (approximately 6 to 12 years) between those who had a prior esophagogastroduodenoscopy and those who had not (adjusted HR 0.93, 95% confidence interval (CI) 0.58–1.50). Though there may be higher odds of a stage 1 diagnosis than a more advanced diagnosis (stage 2–4) if an EGD had been performed in the previous 5 years (OR 2.27, 95% CI 1.00–7.67). Seven studies compared different screening modalities, and showed little difference between modalities. Three studies reported on patients’ unwillingness to be screened (e.g. due to anxiety, fear of gagging). Eleven systematic reviews evaluated treatment modalities, providing some evidence of early treatment effect for some outcomes. Conclusions Little evidence exists on the effectiveness of screening and values and preferences to screening. Many treatment modalities have been evaluated, but studies are small. Overall, there is uncertainty in understanding the effectiveness of screening and early treatments. Systematic review registrations PROSPERO (CRD42017049993 [KQ1], CRD42017050014 [KQ2], CRD42018084825 [KQ3]).